2008
DOI: 10.4049/jimmunol.180.9.5794
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Foxp3-Mediated Induction of Pim 2 Allows Human T Regulatory Cells to Preferentially Expand in Rapamycin

Abstract: Addition of rapamycin to cultures of expanding natural CD4+CD25+Foxp3+ T regulatory cells (Tregs) helps maintain their suppressive activity, but the underlying mechanism is unclear. Pim 2 is a serine/threonine kinase that can confer rapamycin resistance. Unexpectedly, pim 2 was found to be constitutively expressed in freshly isolated, resting Tregs, but not in CD4+CD25− T effector cells. Introduction of Foxp3, but not Foxp3Δ2, into effector T cells induced pim 2 expression and conferred preferential expansion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(114 citation statements)
references
References 25 publications
7
100
0
4
Order By: Relevance
“…[22][23] Moreover, Foxp3 expression induced pim2 expression in Tregs, which allowed for a selective growth advantage of Treg in the presence of rapamycin. 24 It is noteworthy that the elevated expression of CD4 + CD25 + Foxp3 + Treg induced by preoperative treatment of rapamycin sustained at least 2 weeks in peripheral blood, draining lymph nodes, and corneal tissue even after the withdrawal of rapamycin, as shown in the present study. It has been reported that in vivo rapamycin administration contributed to selective activation and expansion of CD4 + CD25 + Foxp3 + Treg, not only in peripheral blood, but also, in secondary lymphoid organs and grafts, both of which merit graft survival.…”
Section: Discussionmentioning
confidence: 56%
“…[22][23] Moreover, Foxp3 expression induced pim2 expression in Tregs, which allowed for a selective growth advantage of Treg in the presence of rapamycin. 24 It is noteworthy that the elevated expression of CD4 + CD25 + Foxp3 + Treg induced by preoperative treatment of rapamycin sustained at least 2 weeks in peripheral blood, draining lymph nodes, and corneal tissue even after the withdrawal of rapamycin, as shown in the present study. It has been reported that in vivo rapamycin administration contributed to selective activation and expansion of CD4 + CD25 + Foxp3 + Treg, not only in peripheral blood, but also, in secondary lymphoid organs and grafts, both of which merit graft survival.…”
Section: Discussionmentioning
confidence: 56%
“…[14][15][16] In fact, in the tumor microenvironment, mTOR inhibition leads to a decrease in the proliferation of CD8 C T cells by direct inhibition coupled with a significant increase in the suppressive regulatory T-cell (Treg) population. 17 Rapamycin has been shown to support the proliferation and survival of Treg cells [18][19][20][21] due to a feedback loop where mTOR inhibition results in PI3K-dependent Akt activation, which sustains signaling through mTOR. 22 Accordingly, antibody-based depletion of Treg cells was proposed recently as a strategy to counteract this inhibition of CD8 C T cells when rapamycin is used to augment memory T cells.…”
Section: E1005448-8 Volume 4 Issue 5 Oncoimmunologymentioning
confidence: 99%
“…1 CD25 1 T cells 14 with a twofold higher expression of pim2 than in CD4 1 CD25 2 T-cells, 6 whereas other reports have not found any differences between these two subsets. 24,25 However, all of the data shown in our experiments demonstrated that pim2 facilitates the allograft rejection, suggesting that this gene may be expressed in effector CD4 1 CD25 2 T cells.…”
Section: Cd4mentioning
confidence: 61%